1994
DOI: 10.1136/oem.51.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to stainless steel welding fumes and lung cancer: a meta-analysis.

Abstract: Stainless steel welding is associated with exposure to metals including hexavalent chromium and nickel. This study is a meta-analysis of five studies of stainless steel welders and the occurrence of lung cancer. Asbestos exposure and smoking habits have been taken into account. The calculated pooled relative risk estimate was 1*94 with a 95% confidence interval of 1-2S-2-93. This result suggests a causal relation between exposure to stainless steel welding and lung cancer. The study showed an association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 8 publications
1
39
0
1
Order By: Relevance
“…Their SMR value (0.89) was lower than welders had experienced in Germany (SMR=1.09) 4) , Norway (SIR=1.13) 21) and Sweden (RR=1.37) 22) , but similar to that in France (SMR=0.93) 19) . Higher lung cancer risk was found among welders in other studies [16][17][18][19] . Sjögren, et al 17) concluded in a meta-analysis that exposure to stainless steel welding fume leads to a higher risk of lung cancer.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Their SMR value (0.89) was lower than welders had experienced in Germany (SMR=1.09) 4) , Norway (SIR=1.13) 21) and Sweden (RR=1.37) 22) , but similar to that in France (SMR=0.93) 19) . Higher lung cancer risk was found among welders in other studies [16][17][18][19] . Sjögren, et al 17) concluded in a meta-analysis that exposure to stainless steel welding fume leads to a higher risk of lung cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Higher lung cancer risk was found among welders in other studies [16][17][18][19] . Sjögren, et al 17) concluded in a meta-analysis that exposure to stainless steel welding fume leads to a higher risk of lung cancer. For 13 yr of follow-up, the evidence is not strong enough yet to indicate that previous shipbreaking work increases the risk of contracting these diseases in this study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The following substances were included as independent risk factors: asbestos (and its interaction with smoking), arsenic (and its interaction with smoking), and cadmium, chromium, crystalline silica, diesel engine exhaust, lead, nickel, radon and welding fumes [mild steel welding (52,77)]. Hexavalent chromium and nickel welders [stainless steel welding (78)] were excluded from the estimate of the size of the chromium-and nickel-exposed populations in Finland. Excluded exposures included, among others, polycyclic aromatic hydrocarbons, man-made mineral fibers, metal dust (replaced by specific studies on exposure to arsenic, cadmium, lead, and nickel), leaded engine exhaust (46), solvent exposure of painters, and fertilizer exposure of chemical process workers.…”
Section: Criteria Used For Selecting the Studiesmentioning
confidence: 99%
“…Stainless steel's main toxicity concern is attributed to Ni and Cr with Material TPI scores of 38.0 and 66.9 per mg, respectively. Ni and Cr (which can be transformed into hexavalent Cr in fumes during stainless steel processing) are both known carcinogens (Sjögren et al 1994;WHO 1997). Stainless steel is used in components such as the brackets and housing for the PulsePoint and RegistRead, respectively.…”
Section: Component Compositions and Materials Tpismentioning
confidence: 99%